Idiopathic sudden sensorineural hearing loss: effectiveness of salvage treatment with intratympanic dexamethasone or hyperbaric oxygen therapy in addition to systemic steroids - Mariani, Cinzia; Carta, Filippo; Catani, Giulia; Lobina, Sara; Marrosu, Valeria; Corrias, Simone; Tatti, Melania; Puxeddu, Roberto (Frontiers in Neurology, 2023)
Background The development of standardized treatments for idiopathic sudden sensorineural hearing loss (ISSNHL) is hampered by uncertainty over the etiology of this disorder. Systemic steroids are historically the primary therapy, with variable hearing outcomes. Over the last two decades, intratympanic steroids (ITS) and hyperbaric oxygen therapy (HBOT) have been proposed as salvage treatments in case of failure of systemic steroids. The present study aims to evaluate the effectiveness of these salvage treatments in addition to systemic steroids. Methods We performed a retrospective study on 75 consecutive patients with a diagnosis of ISSNHL who were admitted to the Department of Otorhinolaryngology of our hospital between December 2018 and December 2022. All patients received primary treatment with systemic steroids. In case of slight or no hearing recovery within the 5th day from the beginning of the therapy (T1), a salvage treatment with ITS or HBOT was proposed. Patients were divided into three groups according to the therapy received: systemic steroids (group A), systemic steroids + HBOT (group B), and systemic steroids + ITS (group C). Pure-tone average at 500, 1000, 2000, and 3000 Hz and the mean gain were evaluated at T1 and 3 months after the beginning of the salvage treatment (T2). The hearing recovery was assessed according to the Siegel's criteria. Results Sixty-two patients (31 men and 31 women, mean age 56 years) with failure of the primary treatment were definitively enrolled in the study: 34 (54.8%) in group A, 16 (25.8%) in group B, and 12 (19.4%) in group C. The ratio of patients responding to therapy was higher in group A (29.4%) than in groups B (18.75%) and C (16.7%). We did not find any statistically significant difference between groups in terms of mean hearing gain at T2 (17.4 ± 15.4 dB in group A vs. 18.6 ± 21.1 dB in group B and 15.7 ± 14.2 dB in group C, p = 0.9). Conclusion In our experience, ITS or HBOT associated with systemic steroids, as salvage treatment, did not show significant improvement in hearing outcomes. The evolution of ISSNHL, regardless of the treatment, remains unpredictable.